The walking dead. Vol. 18, What comes after - Kirkman, Robert (Kirkman, Robert. Walking dead., 2013)
The world we knew is gone. The world of commerce and frivolous necessity has been replaced by a world of survival and responsibility. An epidemic of apocalyptic proportions has swept the globe, causing the dead to rise and feed on the living. In a matter of months society has crumbled: no government, no grocery stores, no mail delivery, no cable TV. In a world ruled by the dead, the survivors are forced to finally start living. Following the events of "Something to Fear," Rick and the other survivors start their new life under Negan and the Savior's rule--but not everyone agrees to go along. Also, who is Ezekiel? And why does he have a tiger?